Achieving Operational Excellence Through Artificial Intelligence: Driving Forces and Barriers - Tariq, Muhammad Usman; Poulin, Marc; Abonamah, Abdullah A. (Frontiers in Psychology, 2021)
The paper presents an in-depth literature review on the driving forces and barriers for achieving operational excellence through Artificial Intelligence (AI). Artificial Intelligence is a technological concept spanning Operational Management, Philosophy, Humanities, Statistics, Mathematics, Computer Sciences, and Social Sciences. AI refers to machines mimicking human behavior in terms of cognitive functions. The evolution of new technological procedures and advancements in producing intelligence for machines creates a positive impact on decisions, operations, strategies, and management incorporated in the production process of goods and services. Businesses develop various methods and solutions to extract meaningful information such as Big Data, automatic production capabilities, and systematization for business improvement. The progress in organizational competitiveness is apparent through improvements in firm’s decisions, resulting in increased operational efficiencies. Innovation with AI has enabled small businesses to reduce operating expenses and increase revenues. The focused literature review reveals the driving forces for achieving operational excellence through AI are: improvement in computing abilities of machines, development of data-based AI, advancements in deep learning, cloud computing, data management, and integration of AI in operations. The barriers are mainly cultural constraints, fear of the unknown, lack of employee skills, and strategic planning for adopting AI. The current paper presents an analysis of articles focused on AI adoption in production and operations. We selected articles published between 2015 and 2020. Our study contributes to literature reviews on operational excellence, Artificial Intelligence, driving forces for AI, and AI barriers in achieving operational excellence.